INNV-26. IN VITRO CHEMO RESISTANCE PROFILES OF CIRCULATING GLIAL CELLS REPLICATE CHEMO CHARACTERISTICS OF TUMOR TISSUE. (11th November 2019) - Akolkar, Dadasaheb; Patil, Sanket; Mhase, Vishakha; Devhare, Pradip; Fulmali, Pooja; Patil, Revati; Srinivasan, Ajay; Datta, Vineet; Schuster, Stefan; Bhatia, Jatinder; Datar, Rajan
Abstract: Survival of high-grade glioma patients remains dismal due to onset of resistance to even the limited systemic treatment option currently available. Except for indirect prediction of alkylating agent Temozolomide response through MGMT promotor methylation and NTRK fusions for larotrectinib, there are no biomarkers available for drug response prediction. Cell based, in vitro chemosensitivity assays can interrogate the efficacy of an array of cytotoxic drugs. However, the unavailability of live tumor cells for such assays pose challenges in clinical practice. Repeat biopsies are neither advisable nor feasible. Access to Circulating Glial Cells (CGCs) can provide real time insight into the chemo dynamics of the tumor. In this study, we show for the first time that CGCs can be harvested from peripheral blood of glioma patients for chemo response and resistance profiles (CRR) of cytotoxic drugs. CGCs were harvested from 15 ml of peripheral blood from high grade GBM patients (n=9) out of whom cells derived from surgically excised tumor tissue were also available for comparison in 2 patients. CellWizard™ process was adopted for enrichment of CGCs which is based upon epigenetically active media with paradoxical chemo-toxicity that selectively induces lethality in normal cells. This paradoxical cytotoxicity of the medium leads to selective elimination of most leukocytes thus facilitating a label free negative enrichment of CGCs. In vitro chemo sensitivity assay performed on live CGCs and cell death events were determined to evaluate response to different class of chemotherapy drugs. Evaluation of drug response showed very high concordance between tumor derived cells and CGCs in both patients where live tissue was available. In 7 patients where CGCs alone could be evaluated, the response showed replication between in vitro profile compared to treatment antecedents in 5 patients. 2 patients were treatment naïve and the response reflected high sensitivity to Temozolomide.